A HUNDRED YEAR OF SITI NURBAYA: ADAPTATIONS FROM FILMS TO MUSICALS - Ulhaq, Salma Dhiya; Risalah Damar Ratri (UIN Raden Mas Said Surakarta, 2024)
This objective of thi sresearch is to map the development of Siti Nurbaya story within its first hundred years. The data is taken from the adaptations of Siti Nurbaya novel into various forms resulting in intriguing discussions from the Nurbaya Musical Series and song lyrics about Siti Nurbaya. Changes from the novel to adaptation forms involve additions, reductions, and adjustments, which are then discussed. This study reveals: (1) the development of Nurbaya's character from the novel to adaptation forms, impacting the storyline and sociological aspects within these adaptations. (2) The addition of new characters, such as Etek Rahma, Nurbaya's conservative aunt, influences various events and plots within the adaptations. (3) Changes in perspective also create new viewpoints, for example, the followers of Datuk Meringgih who in the novel accept menial jobs for instant pleasure, whereas in adaptations, their motivation shifts to supporting their families. (4)Adjustments from the novel to adaptation forms are made to accommodate contemporary times and shorten the consumption time of literary works, thereby modifying conflicts to be more relevant to current contexts.